The real image of the operation Al-Aqsa flood - Miloud, Benattia Hadj (The International tax journal, 2026)
This paper examines Operation al-Aqsa Flood as a turning point in the Palestinian struggle and in the wider confrontation with Zionism. It argues that the operation should be understood within the long history of occupation, blockade, displacement, and repeated Israeli military assaults on Gaza. The study discusses the humanitarian, political, and legal dimensions of the events that followed 7 October 2023, with particular focus on civilian casualties, forced displacement, destruction of infrastructure, and the targeting of humanitarian organizations, especially UNRWA. It also analyzes the Israeli narratives used to justify military actions and questions their legal and moral validity. The paper highlights international reactions, solidarity movements, and legal efforts that have emerged in response to the war on Gaza. It concludes that Operation al-Aqsa Flood exposed the depth of the Palestinian issue and revealed the limits of international neutrality toward Israeli practices.